Implementasi dan Rekomendasi Perbaikan pada Sistem Informasi E-Pulung Bank Sampah Kuncup Mekar Kelurahan Wates Kota Magelang - Kristianto, Yohanes Ivan Adi; Fikri, Faishal Ikhsanul; Betta, Bellany; Septiani, Ninda Mifna; Hidayah, Selly Mawarni (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
One of complicated issues occurs in Indonesia is waste management. The complexity is caused by various factors, one of which is the amount of waste that is not recycled. A number of alternatives can be used to deal with the waste recycling problem, one of which is the establishment of a waste bank. The Waste Bank of Kuncup Mekar, located in Wates Urban Village, Magelang, is one of several waste banks in the city of Magelang. Like other waste banks, the initiative to establish this waste bank is based on the mission of utilizing waste. However, in its management, the Kuncup Mekar Waste Bank is experiencing problems, even though it has been facilitated by a digital application called E-Pulung. This activity, then, aims to analyze the reasons why the waste bank is experiencing problems. The method used in this activity is a qualitative method with data collection using in-depth interviews and observation. This article finds that the main obstacle in operating this waste bank is the employees' busyness to do work, which together with the lack of manpower, to operate the waste bank. Lastly, the author recommends improving the appearance of the user interface in the E-Pulung application by adding options for garbage collection times and channels for transferring waste coin conversions.